The Relationship Between Health Related Quality of Life and Vertebral Fracture in Male Osteoporotic Patients - Özlem El; Selmin Gülbahar; Canan Altay; Çiğdem Bircan; Funda Köroğlu; Sevinç Karcı; Metin Manisalı; Elif Akalın; Özlen Peker; Serap Alper (Galenos Yayinevi, 2005)
Osteoporosis is the most prevalent metabolic bone disease in older people and osteoporotic fractures can be a major cause of morbidity. Vertebral fractures can adversely affect quality of life by causing pain, reducing physical function and mobility, and affecting activities of daily living.The aim of this study was to evaluate the relationship between vertebral fracture and quality of life in male osteoporotic patients. Fortysix male patients with idiopathic osteoporosis were enrolled in this study. Bilaterally thorasic and lumbar spine radiographs were used to investigate the existence of vertebral compression fracture. Anterior, middle and posterior heights of vertebral bodies (T4-L5) have been measured on lateral spine radiographs and the number of vertebrae with fracture were determined.Bone mineral density was measured by using Dual Energy X Ray Absorbtiometry at the lumbar spine(L1-4) and proximal femur. Quality of life was assessed by using Quality of Life Questionnaire of the European Foundation For Osteoporosis(QUALEFFO). The mean number of vertebral fractures was 2.87±1.85.Patients with vertebral fracture (n=31) had lower physical and social function scores than non-fracture patients (n=14). Pain, general health assessment and mental function scores showed no difference between two groups.There was no correlation between number of fractures and quality of life scores. Osteoporotic vertebral fractures affect quality of life negatively. We suggest that during the treatment and follow up of patients with osteoporosis, quality of life scales should be included in the evaluation.